18F-FDG PET/CT, 99mTc-MIBI, and MRI in the Prediction of Outcome of Patients With Multiple Myeloma. (April 2015) - Fonti, Rosa; Pace, Leonardo; Cerchione, Claudio; Catalano, Lucio; Salvatore, Barbara; De Luca, Serena; Pane, Fabrizio; Salvatore, Marco; Del Vecchio, Silvana
<x xml:space="preserve">Abstract</x> Purpose The aim of this study was to compare the relative contribution of 18F-FDG PET/CT, 99mTc-MIBI, and MRI in predicting progression-free survival (PFS) and overall survival (OS) in multiple myeloma (MM) patients. Patients and Methods Thirty-three newly diagnosed MM patients had been evaluated in a previous study by 18F-FDG PET/CT, 99mTc-MIBI, and spine and pelvis MRI reporting focal lesions and diffuse bone marrow involvement. Twenty-seven patients were then subjected to a mean follow-up period of 58 months, whereas 6 patients were lost. Results 18F-FDG PET/CT, 99mTc-MIBI, and MRI were positive in 26, 24, and 22 patients, respectively, showing diffuse bone marrow involvement in 12, 21, and 17 patients and a total of 185, 56, and 39 focal lesions, respectively. At follow-up, 18 patients showed complete or partial remission, whereas 9 patients developed progressive disease, 7 of which died of myeloma. Univariate and subsequent multivariate analysis showed that 18F-FDG PET/CT focal uptake and 99mTc-MIBI focal and diffuse uptake predicted PFS (P = 0.0006), whereas 18F-FDG PET/CT focal uptake and 99mTc-MIBI focal uptake predicted OS (P = 0.0010). Although MRI diffuse pattern predicted PFS at univariate analysis (P = 0.0376), it was not retained in the model at multivariate analysis. Receiver operating characteristic curve analysis showed that the number of focal lesions best discriminating for PFS and OS prediction was 4 and 11 for 18F-FDG PET/CT and 2 in both cases for 99mTc-MIBI, respectively. By Kaplan-Meier analysis and log-rank testing, PFS and OS at follow-up were significantly better in patients showing a number of focal lesions at 18F-FDG PET/CT or 99mTc-MIBI lower than the respective cutoff (P = 0.03, P = 0.004, and P < 0.0001, respectively). Finally, PFS was significantly better in patients showing absent/faint diffuse 99mTc-MIBI uptake than in those having moderate/intense diffuse uptake (P = 0.0012). Conclusions 18F-FDG PET/CT and 99mTc-MIBI may be useful in predicting PFS and OS in myeloma patients.